Exposure-related forest-steppe: A diverse landscape type determined by topography and climate. (December 2016) - Hais, Martin; Chytrý, Milan; Horsák, Michal
Abstract: Topographic heterogeneity under dry continental climate can create a landscape mosaic called "exposure-related forest-steppe", characterized by a regular pattern of forest on the north- and steppe on the south-facing slopes. Here we identify the climatic and topographic determinants of this landscape type, using a model of the Altai Mountains in southern Siberia because they (1) contain large areas of forest-steppe together with forested and steppe landscapes, and (2) possess well-preserved natural land-cover. Based on the Landsat land-cover classification and digital elevation model we identified areas containing exposure-related forest-steppe and modeled their climatic and topographic thresholds using regression trees. The models showed that in the Altai exposure-related forest-steppe is most common in topographically heterogeneous areas with May–September precipitation of 226–377 mm and a mean July temperature of 13.8–15.6 °C. Its existence is jointly determined by hilly topography and a climate that is moist enough to support tree growth on north-facing slopes, but insufficiently so to support woodland development on south-facing slopes. This is consistent with the concept of effective topographic heterogeneity, suggesting that topographic heterogeneity on the landscape level is translated into high habitat diversity and species diversity only within a certain range of climatic conditions. Highlights: Exposure-related forest-steppe is a highly diverse landscape type in semi-arid areas. Its south-facing slopes are covered by grassland and north-facing slopes by woodland. We identified climatic determinants of this landscape type in southern Siberia. It occurs in areas with intermediate precipitation and intermediate temperature. Forest-steppe increases the effective heterogeneity of semi-arid landscapes.